The Influence of Digital Entrepreneurship and Digital Literacy on MSME Performance through Digital Technology Adoption in Indonesia - Imam Muhtadin; Zainal Arifin; Fenty Astrina; Cikita Berlian Hakim; Munzir Munzir; Eko Sudarmanto (Eastasouth Institute, 2026)
This study aims to examine the effect of digital entrepreneurship and digital literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) through the adoption of digital technology in Indonesia. A quantitative research approach was employed using primary data collected from 155 MSME actors through a structured questionnaire measured on a Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both the measurement and structural models. The results indicate that digital entrepreneurship and digital literacy have positive and significant effects on MSME performance. Furthermore, both variables significantly influence the adoption of digital technology, which in turn has a strong positive impact on business performance. The findings also confirm that digital technology adoption plays a mediating role in strengthening the relationship between digital entrepreneurship and MSME performance, as well as between digital literacy and MSME performance. Among the variables, digital literacy shows a stronger influence on technology adoption, highlighting the importance of digital skills in driving digital transformation. This study contributes to the literature by providing an integrated model that explains how digital capabilities influence MSME performance through technology adoption in a developing country context. Practically, the findings suggest that enhancing digital literacy and promoting digital entrepreneurial orientation are essential strategies for improving MSME competitiveness and sustainability in the digital economy.